China's strategy in the Arctic: threatening or opportunistic?. (20th October 2015) - Lasserre, Frédéric; Huang, Linyan; Alexeeva, Olga V.
ABSTRACT: In a context of rapid climatic change in the Arctic, the fast melting of permafrost, the decline of glaciers and the melting of sea ice created perceived strategic and economic opportunities for the littoral states. The attention of states beyond the region was also attracted. For example China, without direct access to the Arctic, displays an interest in Arctic research, natural resources, and shipping potential. However, its diplomatic, economic, political and scientific efforts in this region arouse negative reactions among western media. They often draw up a portrait of an ambitious and arrogant China, ready to push aside the sovereignty of the Arctic countries to defend its own interests in the Arctic. From this perspective, it seems relevant to analyse China's activities in the region and to try to assess Beijing's strategy, which seems more driven by opportunism than by a long-term desire to challenge the littoral states' sovereignty.